Exotic fluorescence spectrum of a superconducting qubit driven simultaneously by longitudinal and transversal fields - Yan, Yiying (2018)
We study the fluorescence spectrum from a two-level system with a controllable energy separation modulated by the longitudinal field and excited by the transversal field. Combining the rotating-wave approximation and the Floquet theory, we derive a formal solution to the Bloch equations in the presence of both longitudinal and transversal driving fields and numerically evaluate the fluorescence spectrum. Exotic spectral features associated with the added longitudinal driving are found to be dramatically different from the standard Mollow triplet with a multipeak structure. The spectrum may be experimentally realized in the context of artificial atoms in a superconducing circuit.